Oxidative gasification of olive mill wastewater as a biomass source in supercritical water: Effects on gasification yield and biofuel composition - Kipcak, Ekin; Akgun, Mesut (ELSEVIER SCIENCE BV, 2012)
In this study the partial oxidation of a biomass source, namely olive mill wastewater (OMW) was investigated in supercritical water. OMW is a by-product obtained in olive oil production and it has a very complex nature that is characterized by a high content of polyphenols and organic compounds. The partial oxidation experiments were carried out at five different reaction temperatures (400, 450, 500, 550 and 600 degrees C) and five different oxygen concentrations (9.11, 18.22, 45.55, 91.10 and 182.20 mmol O-2/L) with a reaction time of 30 s, under a pressure of 25 MPa. In addition, various OMW concentrations were tested in order to comprehend the effects on biofuel yield and composition. The gaseous products were generally composed of hydrogen, carbon monoxide, carbon dioxide and C-1-C-4 hydrocarbons like methane, ethane, propane and propylene. The maximum yield of the obtained gaseous product was 5.55 m(3)/kg carbon in OMW with feed total organic carbon (TOC) concentration of 2500 mg/L, at a temperature of 550 degrees C. At these reaction conditions, the aforementioned product composition was 7.93% for hydrogen, 28.91% for methane, 5.85% for ethane, 0.47% for propane, 0.55% for propylene, 54.04% for carbon dioxide and 0.16% for minor components such as n-butane, i-butane, 1-butene, i-butene, t-2-butene, 1,3-butadiene and nitrogen. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biofuels; Gasification; Olive mill wastewater; Partial oxidation; Supercritical water; HYDROGEN-PRODUCTION; CELLULOSE; GLUCOSE; COAL; Chemistry; Engineering